2018
DOI: 10.1148/radiol.2017162971
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Presurgical Functional MR Imaging for Language Mapping of Brain Tumors: A Systematic Review and Meta-Analysis

Abstract: Purpose To compare functional magnetic resonance (MR) imaging for language mapping (hereafter, language functional MR imaging) with direct cortical stimulation (DCS) in patients with brain tumors and to assess factors associated with its accuracy. Materials and Methods PubMed/MEDLINE and related databases were searched for research articles published between January 2000 and September 2016. Findings were pooled by using bivariate random-effects and hierarchic summary receiver operating characteristic curve mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…Previous research has shown that language fMRI mapping, in particular, can vary significantly due to varied statistical thresholds, imaging times, and specific language task being performed. 23 Nevertheless, the present study does provide valuable information as how the distance used has a profound impact on the accuracy measures that surgeons may take into account even without assuming the uniformity of their data to that of the present study.…”
Section: Modalitymentioning
confidence: 84%
“…Previous research has shown that language fMRI mapping, in particular, can vary significantly due to varied statistical thresholds, imaging times, and specific language task being performed. 23 Nevertheless, the present study does provide valuable information as how the distance used has a profound impact on the accuracy measures that surgeons may take into account even without assuming the uniformity of their data to that of the present study.…”
Section: Modalitymentioning
confidence: 84%
“…FMRI based on the measurement of BOLD contrast is one of the most widely applied non‐invasive techniques to localize eloquent cortices for presurgical planning . By intermittently engaging patients in task and control conditions, task‐based FMRI has been shown to correlate well with intraoperative direct cortical stimulation . However, its practicality for presurgical language mapping is compromised when patients have inadequate compliance because of impaired cognitive, perceptual, and/or motor functions .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 By intermittently engaging patients in task and control conditions, task-based FMRI has been shown to correlate well with intraoperative direct cortical stimulation. 3,4 However, its practicality for presurgical language mapping is compromised when patients have inadequate compliance because of impaired cognitive, perceptual, and/or motor functions. 5,6 Resting-state FMRI (rs-FMRI) has been considered as an adjunct to task-based FMRI for presurgical evaluations because it provides a means of functional mapping without task engagements by measuring the distant synchronization of low-frequency BOLD oscillations throughout the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is a powerful diagnostic tool and with a wide array of clinical, mainly diagnostic, applications . While MRI‐guided procedures (interventional MRI) began in the 1990s, image‐guided interventions are still dominated by ultrasound, fluoroscopy, and computed tomography (CT) .…”
mentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is a powerful diagnostic tool and with a wide array of clinical, mainly diagnostic, applications. [2][3][4][5][6][7][8][9][10] While MRI-guided procedures (interventional MRI) began in the 1990s, image-guided interventions are still dominated by ultrasound, fluoroscopy, and computed tomography (CT). 11 There are several challenges to MR-guided interventions, such as longer acquisition times, increased cost of MRI-safe equipment, and the technical complexity of performing a procedure within a superconducting MRI system.…”
mentioning
confidence: 99%